2011
DOI: 10.1080/15567030903397974
|View full text |Cite
|
Sign up to set email alerts
|

The Environmentally Significant Element Contents of Eocene Coals in North Anatolia, Turkey

Abstract: The North Anatolia region in Turkey contains a large amount of highcalorie lignite coal deposits of the Eocene age. In this study, distribution of the environmentally significant element contents of Eocene coals, enrichment factors of these elements, and relation between total organic carbon and these elements were investigated. Contents of environmentally harmful elements, such as Mo, V, B, Se, and S contents of the Amasya-Bogaköy and Bolu-Salıpazarı, are found to be lower than that of average concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
1
1
Order By: Relevance
“…Gruas‐Cavagnetto, 1988; Hochuli, 1978; Nickel, 1996; Roche, 1988; Schuler, 1988; Wilkinson & Boulter, 1980). The presence of the above‐mentioned taxa indicates that the age of the Aspiras Basin might be younger than Eocene, as opposed to previous studies (Hoş Çebi, 2007; Hoş Çebi & Korkmaz, 2011, 2013). Moreover, some Juglandaceae pollen species such as Momipites punctatus ( Engelhardia ), Momipites quietus ( Engelhardia ), and Subtriporopollenites anulatus nanus (?…”
Section: Biostratigraphycontrasting
confidence: 70%
See 1 more Smart Citation
“…Gruas‐Cavagnetto, 1988; Hochuli, 1978; Nickel, 1996; Roche, 1988; Schuler, 1988; Wilkinson & Boulter, 1980). The presence of the above‐mentioned taxa indicates that the age of the Aspiras Basin might be younger than Eocene, as opposed to previous studies (Hoş Çebi, 2007; Hoş Çebi & Korkmaz, 2011, 2013). Moreover, some Juglandaceae pollen species such as Momipites punctatus ( Engelhardia ), Momipites quietus ( Engelhardia ), and Subtriporopollenites anulatus nanus (?…”
Section: Biostratigraphycontrasting
confidence: 70%
“…Özen (1975) first investigated the potential of lignites with their qualities and put the basin in the Eocene without any indication of fossil and radiometric data. By accepting Özen's prediction concerning the age, Hoş Çebi and Korkmaz (2011, 2013) interpreted the geochemical characteristics and depositional environments of the Aspiras Basin. In contrast, other researchers indicated that the sediments in the basin were deposited during the Miocene (sensu lato) based on the limited information on the ostracods, pollen, mammals, micromammals and radiometric ages (Akyürek et al, 1980, 1996; Deleuil, 1977; Ercan et al, 1990; Karadenizli et al, 2004; Sevin & Uğuz, 2011; Türkecan et al, 1991).…”
Section: Introductionmentioning
confidence: 98%